2021
DOI: 10.1007/s10266-020-00585-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of vasopressin on anesthetic response time and circulatory dynamics of lidocaine

Abstract: This study aimed to investigate the hypothesis that vasopressin extends the anesthetic response time of lidocaine and does not affect the circulatory dynamics. Rats were sedated with isoflurane; subsequently, breathing was maintained through mechanical ventilation. We infiltrated the first molar area of the upper left jaw with saline (NS, test solution), 2% lidocaine (L), 0.025 IU vasopressin-supplemented 2% lidocaine, 0.05 IU vasopressin-supplemented 2% lidocaine, 0.1 IU vasopressin-supplemented 2% lidocaine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
1
0
4
Order By: Relevance
“…A literatura que postula que pacientes com alterações sistêmicas devem receber atendimento odontológico levando-se em conta o cuidado na via de administração, dose e uso de vasoconstritores. A lidocaína é um anestésico local amplamente utilizado na Odontologia devido à sua alta penetração nos tecidos e rápido início de ação 6 . No entanto, o efeito vasoconstritor da epinefrina pode ocasionar elevação da pressão arterial, restringindo seu uso em pacientes com hipertensão e doença cardíaca isquêmica.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A literatura que postula que pacientes com alterações sistêmicas devem receber atendimento odontológico levando-se em conta o cuidado na via de administração, dose e uso de vasoconstritores. A lidocaína é um anestésico local amplamente utilizado na Odontologia devido à sua alta penetração nos tecidos e rápido início de ação 6 . No entanto, o efeito vasoconstritor da epinefrina pode ocasionar elevação da pressão arterial, restringindo seu uso em pacientes com hipertensão e doença cardíaca isquêmica.…”
Section: Discussionunclassified
“…No entanto, o efeito vasoconstritor da epinefrina pode ocasionar elevação da pressão arterial, restringindo seu uso em pacientes com hipertensão e doença cardíaca isquêmica. A adição de vasopressina à lidocaína como um vasoconstritor poderia permitir anestesia local odontológica segura em pacientes com doenças cardiovasculares 6 . Murata et al (2020) 24 relataram que a eficácia anestésica da lidocaína foi ampliada ao associar 0,03 UI / mL de vasopressina.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Local anesthetics containing AVP may increase the anesthetic effect, prolong the duration of action, control bleeding, and prevent toxicity without affecting hemodynamics, particularly cardiac function [ 13 14 ]. Conversely, Fujimori et al [ 15 ] reported increased blood pressure and decreased pulse rate following AVP injection into the oral cavity of rats. In addition, Walker et al [ 16 ] demonstrated that AVP stimulates cardiac function via V1a receptors.…”
Section: Introductionmentioning
confidence: 99%